Creation stories in dialogue : the Bible, science, and folk traditions : Radbound prestige lectures in New Testament - Culpepper, R. Alan. (Biblical Interpretation Series, 2015)
This book is about creation stories in dialogue, not only between different religious views, but also between current day scientific perspectives. International specialists, like Alan Culpepper, David Christian, John Haught, Randall Zachman, Ellen van Wolde from various disciplines are reflecting on the interface between science and religion relating questions of creation and origin. This multi-disciplinary discussion by some of the leading exponents in this field makes the book unique, not only in its depth of discussion, but also in it wide ranging interdisciplinary discussion. The point of departure of all the contributions is the prestige lecture by Alan Culpepper where he argues for bringing Biblical material into discussion with modern scientific insights relating to creation and origin.